Psychotropic polypharmacy in people with neuropsychiatric symptoms referred to an Australian dementia support service. (20th December 2022) - Atee, Mustafa; Andreotta, Matthew; Morris, Thomas; Alford, Marie
Abstract: Background: Despite limited evidence, psychotropics, such as antipsychotics are commonly used to treat neuropsychiatric symptoms (NPS) in people living with dementia. There are safety concerns on the use of antipsychotics, but co‐prescribing multiple classes of psychotropics (psychotropic polypharmacy) may have a greater and more serious harm to this group. This includes sedation‐induced falls, delirium, hospitalizations, and mortality. In Australia, people with significant NPS, such as agitation and aggression can be referred for free 24/7 support and advise to a national behavior dementia‐specific support service known as Dementia Support Australia (DSA). The aim of this study is to describe the prevalence of psychotropic polypharmacy in DSA referrals. Method: We used a sample of medication charts from the DSA database to estimate the prevalence of psychotropic polypharmacy in referrals between January and November 2020. A descriptive analysis of psychotropic use was based on the grouping of the World Health Organization Anatomical Therapeutic Classes (ATCs), which included seven classes: antipsychotics, antidepressants, anxiolytics, opioid analgesics, hypnotics, anticonvulsants, and anti‐dementia drugs. Psychotropic polypharmacy was defined as the concomitant use of ≥2 psychotropics overall, whether it is within the same class, subclass, or cross‐class. Results: Of the 137 referrals [ M = 83.6 ( SD = 8.5) years of age; 54.0% female], 28 referrals were prescribed medications that could not be nearly categorized into the ATCs (e.g., ibuprofen). For the remaining 109 referrals included in analysis, polypharmacy was common ( n = 82, 75.2%; Figure 1A). Polypharmacy was especially common for referrals who were prescribed anxiolytics ( n = 25, 100% prescribed additional medication), anticonvulsants ( n = 27, 96.4% prescribed additional medication), or anti‐dementia ( n = 25, 96.2% prescribed additional medication) medications. Of the 36 different psychotropic medications prescribed to referrals, 23 (63.9%) were prescribed exclusively with additional medications. The most common co‐prescriptions (Figure 1B) were antidepressants+antipsychotics ( n = 6, 5.5%), anti‐dementia+opioid analgesic ( n = 4, 3.7%), antidepressants+antipsychotics+hypnotics ( n = 4, 3.7%), and antipsychotics+hypnotics ( n = 4, 3.7%). Conclusion: Psychotropic polypharmacy is common in people with dementia related NPS who require external behavioral support. Deprescribing psychotropics should be considered a priority in this group as the risks of these agents outweigh their benefits.